Value of plasma homocysteine to predict stroke, cardiovascular diseases, and new-onset hypertension: A retrospective cohort study. Issue 34 (21st August 2020) - Feng, Yuanyuan; Kang, Kai; Xue, Qiqi; Chen, Yafen; Wang, Wei; Cao, Jiumei
Abstract : Abstract: The influences of hyperhomocysteinemia on cardiovascular diseases (CVDs), stroke and new-onset hypertension are unclear. The aim of the study is to explore the associations of homocysteine levels with stroke, CVDs, and new-onset hypertension in Chinese individuals. This retrospective cohort study included outpatients and inpatients from the Department of Geriatrics at Ruijin Hospital affiliated to Shanghai Jiaotong University School of Medicine from January to December 2000. They were divided based on their homocysteine (Hcy) levels in 2000: Q1 (<10 μmol/L), Q2 (10–15 μmol/L), and Q3 (>15 μmol/L) and according to whether they had hypertension at baseline. Information about stroke, mortality and major adverse cardiac events, and newly onset hypertension was gathered in December each year until 2017. The effects of Hcy levels on the risk for stroke and CVDs among all patients, and new-onset hypertension among patients without hypertension at baseline were evaluated. After adjustment for confounders, compared with the Q1 group (Hcy <10 μmol/L), when the Hcy increased to 10 to 15 μmol/L, the risks for stroke, CVDs, and new-onset hypertension significantly increased, and the hazard ratio and 95% confidence interval were 2.02 (1.35–3.05, P  = .001), 2.22 (1.32–3.76, P  = .003), and 7.20 (4.52–11.48, P  < .001), respectively. Hcy improved the predictive capability of traditional risk factors for stroke. The optimal cut-off value of Hcy for predicting stroke was 13.4 μmol/L (sensitivity: 70.9%, specificity: 62.2%). Hcy 10 to 15 μmol/L is significantly associated with the risks for stroke, mortality and major adverse cardiac events, and hypertension. The best cut-off point of Hcy for predicting stroke is 13.4 μmol/L.